Cross-Reaction of Duck and Chicken Sera against Avian Influenza H5N1 Virus Clades 2.1.3 and 2.3.2 Antigens by Hemagglutination Inhibition Test - Indriani, Risa; Dharmayanti, NLP I; Martindah, E. (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTThis study aims to determine the cross-reaction between the antigen of avian influenza (AI) H5N1 virus clades 2.1.3 and 2.3.2 in duck and chicken sera, which were vaccinated with inactivated AI H5N1 clade 2.1.3 vaccine against AI H5N1 clade 2.3.2 antigen and those vaccinated with inactivated AI H5N1 clade 2.3.2 vaccine against H5N1 clade 2.1.3 antigen. The sera tested were obtained from postvaccination and control (unvaccinated) chickens and ducks in the laboratory condition, and from AI H5N1 postvaccination ducks in the field condition. HI test was conducted by using AI H5N1 clades 2.1.3 and 2.3.2 antigens. The results of HI titer were analyzed by the geometric means and by ANOVA. The results show that cross-reactions in both chicken and duck sera after AI H5N1 clade 2.3.2 vaccination tested with AI H5N1 clade 2.1.3 antigen occurred with low antibody titers, whereas in chicken and duck sera postvaccination with avian influenza H5N1 virus clade 2.1.3 showed cross-reaction with high antibody titer against clade 2.3.2 antigen. The conclusion of this study, postvaccination sera of AI H5N1 clade 2.1.3 provide better cross-reaction compared to the postvaccination sera of AI H5N1 clade 2.3.2.Keywords: sera, chicken, duck, AI H5N1, clade 2.1.3 and clade 2.3.2.